Revealing the Unique Characteristics of Greek White Wine Made from Indigenous Varieties Through Volatile Composition and Sensory Properties - Evangelia Nanou; Maria Metafa; Susan E. P. Bastian; Yorgos Kotseridis (Beverages)
Greek wines made from the indigenous grape varieties Assyrtiko, Malagousia, Moschofilero and Roditis are attracting the interest of wine producers and consumers due to their aromatic characteristics. However, there are few studies that focus on the unique wine characteristics of each variety and the relationship between the composition of volatile compounds and sensory properties. Monovarietal white wines (2018 vintage) were analyzed by gas chromatography–mass spectrometry to quantify 34 volatile compounds. Multivariate statistical analyses were used to investigate correlations between volatiles and sensory attributes identified by a trained panel. The results showed that the strongest aroma compounds were a group of terpenes, isoamyl acetate and phenylethyl acetate. Terpenes such as geraniol, α-terpineol, linalool and cis-rose oxide correlated with floral notes, especially in Moschofilero wines. In addition, isoamyl acetate contributed to the aroma of tropical fruits, especially banana, in the Roditis wines, while phenylethyl acetate correlated with rose, vanilla and fruity notes in both the Moschofilero and Roditis samples. The Assyrtiko wines and the Malagousia wines were mainly associated with compounds such as cis-3-hexen-1-ol and cis- and trans-furan linalool oxides, which may enhance fresh fruit and citrus aromas through synergistic effects. The common background aroma of the studied wines was mainly determined by higher alcohols, fatty acids and ethyl esters. This study provides a basis for understanding the typical aroma of white wines from indigenous Greek grape varieties, which will help producers develop targeted wine styles and will be useful for consumer promotion.